2015
DOI: 10.1242/bio.201410991
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of KDM4 lysine demethylases disrupts the integrity of the DNA mismatch repair pathway

Abstract: The KDM4 family of lysine demethylases consists of five members, KDM4A, -B and -C that demethylate H3K9me2/3 and H3K36me2/3 marks, while KDM4D and -E demethylate only H3K9me2/3. Recent studies implicated KDM4 proteins in regulating genomic instability and carcinogenesis. Here, we describe a previously unrecognized pathway by which hyperactivity of KDM4 demethylases promotes genomic instability. We show that overexpression of KDM4A-C, but not KDM4D, disrupts MSH6 foci formation during S phase by demethylating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 58 publications
(75 reference statements)
0
25
0
Order By: Relevance
“…Our findings therefore expand our understanding of how this demethylase family exerts a myriad of effects in cancer tissue. Overexpression/ectopic expression of human KDM4A homologs have been shown to induce transient site-specific amplification of a cytogenetic region containing satellite DNA in tumors and cell lines (Black, Manning et al 2013), antagonize 53BP1 binding to DSBs (Mallette, Mattiroli et al 2012), disrupt mismatch repair (Awwad and Ayoub 2015), and produce chromosomal instability (Slee, Steiner et al 2012) and chromosome missegregation (Kupershmit, Khoury-Haddad et al 2014). Further studies are required to determine if high levels of KDM4A homologs promotes tumor progression solely through altered transcriptional regulation of EC cancer-linked genes, or if defects in HC structure and function also advance genomic evolution of cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings therefore expand our understanding of how this demethylase family exerts a myriad of effects in cancer tissue. Overexpression/ectopic expression of human KDM4A homologs have been shown to induce transient site-specific amplification of a cytogenetic region containing satellite DNA in tumors and cell lines (Black, Manning et al 2013), antagonize 53BP1 binding to DSBs (Mallette, Mattiroli et al 2012), disrupt mismatch repair (Awwad and Ayoub 2015), and produce chromosomal instability (Slee, Steiner et al 2012) and chromosome missegregation (Kupershmit, Khoury-Haddad et al 2014). Further studies are required to determine if high levels of KDM4A homologs promotes tumor progression solely through altered transcriptional regulation of EC cancer-linked genes, or if defects in HC structure and function also advance genomic evolution of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Members of this family play vital roles in epigenetic mechanisms that govern gene expression and development (Nottke, Colaiacovo et al 2009, Lorbeck, Singh et al 2010), regulate DNA repair and genome stability (Mallette, Mattiroli et al 2012, Kupershmit, Khoury-Haddad et al 2014, Awwad and Ayoub 2015), and are misregulated in many types of cancers (Black, Manning et al 2013, Guerra-Calderas, Gonzalez-Barrios et al 2015). Despite its name, the closest dKDM4A mammalian homolog is KDM4D, since both contain the JmjN and JmjC domains responsible for enzymatic activity, and lack the PHD and Tudor domains found in human KDM4A (Lloret-Llinares, Carré et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of these genes, which is a relative common event in various types of cancer [114], may thus interfere with all processes that involve H3K36me3 readers. As an example, it was recently shown that an enhanced expression of KDM4A-C promotes genomic instability [115]. By demethylating H3K36me3 the recruitment of MSH6 is prevented.…”
Section: Setd2 In Cancermentioning
confidence: 99%
“…Down-regulation of SETD2 by long non-coding RNA (LncRNA) HOTAIR leads to MSI and MMR deficiency [46]. Similarly, depletion of H3K36me3 by overexpressing H3K36me2/3 demethylases, KDM4A-C, disrupts MSH6 chromatin localization and induces a mutator phenotype [47]. Taken together, these observations strongly suggest that the H3K36me3 histone mark plays a critical role in MMR in vivo.…”
Section: Role Of Histone Modifications In Mmr In Vivomentioning
confidence: 99%